Molecular mechanisms of initiation of fibrinolysis by fibrin - Medved, Leonid; Nieuwenhuizen, Willem (Thrombosis and Haemostasis, 2003)
Fibrinogen is rather inert in the circulation, however, after conversion into fibrin it participates in various physiological processes including fibrinolysis. Initiation of fibrinolysis occurs through a number of orchestrated interactions between fibrin, plasminogen and its activator tPA which result in generation of plasmin. Numerous studies localized a set of specific low affinity tPA- and plasminogen-binding sites in each D region of fibrin(ogen). The tPA-binding site includes residues γ312-324 and the plasminogen-binding site includes residues Aα148-160; they bind tPA and plasminogen with a Kd of about 1 μM. Another set of high affinity tPA- and plasminogen-binding sites (Kds = 16-33 nM) was identified in the compact portion of each fibrin(ogen) αC-domain within residues Aα392-610. All these sites are cryptic in fibrinogen and become exposed in fibrin. Recent studies with recombinant and proteolytic fibrin(ogen) fragments clarified the molecular mechanisms by which these sites become exposed. Namely, upon fibrin assembly, the interaction between the D and E regions causes conformational changes in the former that expose the low affinity binding sites. The exposure of the high affinity binding sites in the αC-domains is connected most probably with their switch from an intramolecular interaction in fibrinogen to an intermolecular one in fibrin. These mechanisms serve to minimize degradation of circulating fibrinogen and confine fibrinolysis to places of fibrin deposition.
Keywords: Fibrinogen; fibrin; plasminogen; tPA; fibrinolysis